2012
DOI: 10.1017/s1049023x12000957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Active Mortality Surveillance System Data for Monitoring Hurricane-Related Deaths—Texas, 2008

Abstract: Introduction-The Texas Department of State Health Services (DSHS) implemented an active mortality surveillance system to enumerate and characterize hurricane-related deaths during Hurricane Ike in 2008. This surveillance system used established guidelines and case definitions to categorize deaths as directly, indirectly, and possibly related to Hurricane Ike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…This expectation of having timely and accurate hurricane-related death counts immediately following a catastrophic disaster represents a failure among scientists and communicators to convey the inherent superiority of excess mortality estimation over "body counts" in complex disaster scenarios where surveillance systems and death certification processes are disrupted (Checchi & Roberts, 2008). Currently, there is little to guide communicators in making this distinction apparent to public audiences; while there is scientific literature related to mortality surveillance (Choudhary, 2012;Farag et al, 2013;Kim et al, 2017;Rocha et al, 2017;Seil et al, 2016) and documenting cause of death (Centre for Research on the Epidemiology of Disasters [CRED], 2016;Lakkireddy et al, 2004;Phillips et al, 2014;Wexelman et al, 2013), there is a paucity of studies exploring the specific concept of communicating disaster mortality to the public. There is no literature base that examines how death counts from a disaster should be communicated to the media, how to best explain information gaps that are common following disasters, how death counts may evolve post-disaster, or how to explain the science behind excess death estimates and what we can or cannot infer from these estimates.…”
Section: Communication Of Disaster Mortality To the Publicmentioning
confidence: 99%
“…This expectation of having timely and accurate hurricane-related death counts immediately following a catastrophic disaster represents a failure among scientists and communicators to convey the inherent superiority of excess mortality estimation over "body counts" in complex disaster scenarios where surveillance systems and death certification processes are disrupted (Checchi & Roberts, 2008). Currently, there is little to guide communicators in making this distinction apparent to public audiences; while there is scientific literature related to mortality surveillance (Choudhary, 2012;Farag et al, 2013;Kim et al, 2017;Rocha et al, 2017;Seil et al, 2016) and documenting cause of death (Centre for Research on the Epidemiology of Disasters [CRED], 2016;Lakkireddy et al, 2004;Phillips et al, 2014;Wexelman et al, 2013), there is a paucity of studies exploring the specific concept of communicating disaster mortality to the public. There is no literature base that examines how death counts from a disaster should be communicated to the media, how to best explain information gaps that are common following disasters, how death counts may evolve post-disaster, or how to explain the science behind excess death estimates and what we can or cannot infer from these estimates.…”
Section: Communication Of Disaster Mortality To the Publicmentioning
confidence: 99%
“…• Injuries and poisonings Monitoring disaster mortality through vital registration systems alone has been shown to result in the potential underestimation of impacts (Choudhary et al 2008). ''Active mortality surveillance systems'' can be established, which provide guidance to physicians and medical examiners on causes of death and mortality codes likely to arise because of a disaster.…”
Section: Civil Registration and Vital Statistics Systemsmentioning
confidence: 99%
“…These have been shown to result in the identification of a significantly higher number of disaster deaths than gleaned from CRVS alone. For example, during Hurricane Ike in 2008, a review of vital statistics data found only four deaths in Texas to be hurricane related, but a rapidly implemented active mortality surveillance system identified 74 hurricane-related deaths (Choudhary et al 2008).…”
Section: Civil Registration and Vital Statistics Systemsmentioning
confidence: 99%
“…These studies described how mortality surveillance systems successfully identified hurricane-related deaths and allowed jurisdictions to rapidly direct their public health response. In addition, the detailed information collected as part of the disaster surveillance system was a valuable resource for assessing disaster-related deaths because it includes more information about the circumstances of the death than reported on the death certificates (6). …”
Section: Resultsmentioning
confidence: 99%